EFFECT OF MIX MARKETING ON RE–PURCHASE DECISION OF MUSLIM DRESS IN BOGOR (MUSLIM CLOTHING PRODUCT OF KEKE) - Indarto Setiawan; Budi Suharjo; Mukhammad Najib (School of Business, IPB University (SB-IPB), 2016)
The main objective of this study was to analyze the factors that determines consumers in their purchasing decisions Muslim dress and recommend the proposed marketing mix strategy affects customer satisfaction and loyalty which can have an impact on purchasing decisions / repurchase (repurchase) by consumers. The analytical methods used in this study Chi-Square Test, Thurstone Case-V Analysis, Correspondence Analysis, and Structural Equation Model. The results showed the purchasing decisions Muslim clothing there is a relationship between level of education and average revenue / expenditure per month with custom usage Muslim clothing, there are five sequences attribute Muslim clothing that is essential according to the respondents, the underwear model, quality of materials, patterns typical, leisure time used as well as an attractive packaging design. Muslim clothing brand Ke'ke is purchased by consumers because the ads fit the facts, reasonably priced, there are many models of quality koko and containerized, while shortcomings are in the variation of the veil / hijab and less spread of sales outlets. The products are very dominant. They influence purchasing decisions of consumers so that the superiority of the product should be maintained and even improved.Keywords: muslim clothing, the mix marketing, re-purchasing decisions